A IMPORTÂNCIA DOS ATRIBUTOS E SERVIÇOS DA AVALIAÇÃO DA QUALIDADE: UM ESTUDO NO SETOR BANCÁRIO DE TRÊS PASSOS - Schmaedecke, Daniel A.; Albring, Jeferson L.; Borger, Luis A.; Simsen, Daniela; Marquezin, Cristiane; Zamberlan, Luciano (Salão do Conhecimento, 2013)
Resumo